INFLUENŢA STRUCTURILOR SECURITĂŢII INTERNAŢIONALE CONTEMPORANE ASUPRA STATELOR POSTSOVIETICE CU O CAPACITATE GEOPOLITICĂ MODESTĂ - Mija, Valeriu (CEP USM, 2016)
National states with a geopolitical modest capacity are more capable to strategically adapt to international security environment than to shape or to influence it. Respectively, prospects of such states, such as the Republic of Moldova, will depend on the evolution of contemporary security environment as well as on ability to promote policies of strategic adaptation. International security environment assessment demonstrates that historical key transformations and new challenges contribute to the formation of a particular international world order with an international regime, which is a foundation of the structure of the international system. The latter, directly or indirectly, influence European and post-Soviet states. The Analysis of modern international security through the main paradigms of international relations theory determines that current European security system structure has international neoliberal regime as its foundation, which respectively influence over European small states. Meantime, the regional situation around the Republic of Moldova and Ukraine are sensitive because two different international systemic structures - EU / NATO and the CIS - have geopolitical border zone around both countries. The prospects of small states positioned within the EU systemic structure will be much similar due to international neoliberal regime’s influence on states’ foreign policy. The EU with its principles, norms, rules and decision-making procedures of solidarity eventually remodels European national identities and foreign policies toward collective and solidary ones. Correspondingly, foreign and security policies of most European states will be influenced by the effects of international neoliberal structure, if international status quo continues. Prospects of some former Soviet states in the contemporary international security environment can be more precisely assessed by comparing with the experience of some European states during bipolarity.
Keywords: geopolitical capacity; international security; small states